Nilai Religi dalam Novel Mengejar Halalnya Syabila Karya Noor Ruhaimin - Heppy Lismayanti; Haris Supratno; Tengsoe Tjahjono (STILISTIKA: Jurnal Bahasa, Sastra, dan Pengajarannya, 2019)
This study examines the religious values ​​contained in the novel Mengejar Halalnya Syabila by Noor Ruhaimin. The purpose of this study is to: (1) describe aqidah, (2) describe worship, and (3) describe morals in the novel Mengejar Halalnya Syabila by Noor Ruhaimin. The method in this research is descriptive analysis method. The data source in this study is the novel Mengejar Halalnya Syabila by Noor Ruhaimin. This novel was published by BanyuwangiNaa Publisher in 2018. The collection technique in this research is the text observation technique and the data analysis technique used is interpretive descriptive technique. Based on the research results obtained: Religious values ​​associated with aqidah namely, (a) faith in God, (b) faith in books. (c) faith in the Rasul, and (d) faith in qada and qadar. Religious values ​​related to worship are, (a) public worship, such as helping in the family (b) special worship. Religious values ​​related to morals, namely, (a) morals towards God. (b) the morals of both parents. (c) morals towards oneself (d) morals towards family and relatives. (e) morals towards the community